People’s Multiparty Democracy: An Instrument for Social Transformation - Pahari, Bharat Raj (State, Society and Development: PMPD Perspectives, 2024)
Madan Bhandari, then General Secretary of the CPN (UML), critically analyzed the World Communist Movement and the Nepali Communist Movement and formulated the People’s Multiparty Democracy (PMPD) to build a just and egalitarian democratic society. It was first approved by the Fifth National General Convention of the CPN (UML) as the party’s program in 1993. The Fourth National General Convention of the CPN-ML provided direction for the ideas and perspectives of PMPD in 1989. Based on those ideas, the left-wing parties formed the United Left Front in 1989 and later extended a working alliance with the Nepali Congress Party for the joint movement for the restoration of multiparty parliamentary democracy. When the USSR and the communist regimes in Eastern Europe were falling, the CPN (UML) came to power in Nepal through the election. According to Marxist theory, the source of discrimination, exploitation, and oppression in society is the form of ownership of the means of production and resources and the mode of production. In the early 1990s, Bhandari further explained Marxist political philosophy by stating that plurality results from the diversity existing in nature, which creates differentiation and is an inherent basis of exploitation and oppression. To address this phenomenon in politics, Bhandari added ideas of democratic practices of competition and initiative by redefining Marxist-Leninist philosophy. Bhandari applied the method of democratization in party and leadership development through internal competition, thus making the party popular in the country. Drawing insights from various resource materials, this paper explores the interrelationships between politics and philosophy from PMPD perspectives.